A MULTICULTURAL SOCIETY AND SCHOOLS - Abdurrahman; Zainal Hakim; Tho N. Nguyen (The Islamic Education and Multiculturalism Foundation, 2022)
This report has been developed based on a library research investigation of numerous library materials related to communities and schools that conflict with multicultural terminology. The approach states that the data collection methods used in this study are documented procedures, in which data is obtained through documents known as library materials. Data from this study are analyzed using content analysis. It became clear that multicultural schools and communities are higher education establishments that acknowledge and are willing to accept the existence of a wide variety of diverse identities in the communit